A minireview of the medicinal and edible insects from the traditional Chinese medicine (TCM) - Zhang, Enming; Ji, Xin; Ouyang, Fang; Lei, Yang; Deng, Shun; Rong, Haibo; Deng, Xuangen; Shen, Hai (Frontiers in Pharmacology, 2023)
Entomoceuticals define a subset of pharmaceuticals derived from insects. The therapeutic effect of insect-derived drugs has been empirically validated by the direct use of various folk medicines originating from three sources in particular: the glandular secretions of insects (e.g., silk, honey, venom), the body parts of the insect or the whole used live or by various processing (e.g., cooked, toasted, ground), and active ingredients extracted from insects or insect-microbe symbiosis. Insects have been widely exploited in traditional Chinese medicine (TCM) relative to other ethnomedicines, especially in the prospect of insect species for medicinal uses. It is noticeable that most of these entomoceuticals are also exploited as health food for improving immune function. In addition, some edible insects are rich in animal protein and have high nutritional value, which are used in the food field, such as insect wine, health supplements and so on. In this review, we focused on 12 insect species that have been widely used in traditional Chinese herbal formulae but have remained less investigated for their biological properties in previous studies. We also combined the entomoceutical knowledge with recent advances in insect omics. This review specifies the underexplored medicinal insects from ethnomedicine and shows their specific medicinal and nutritional roles in traditional medicine.